Induced sex reversal and breeding of greasy grouper Epinephelus tauvina (Forskal) - Kailasam, M; Arasu, A R T; Abraham, Mathew; Sultana, Munawar; Shiranee, P; Balakrishnan, M; Thiagarajan, G; Karaiyan, K; Subburaj, R (Indian Journal of Fisheries, 2011)
Hormone doses required for induced breeding and induced sex reversal of femalesto males in the greasy grouper Epinephelus tauvina were standardized. Spawningwas induced by multiple injection of HCG at doses ranging from 700 and 2400IU/kg body weight and LHRHa @ 30-40μg/kg body weight. Females with initialmean ova diameter of 450 μm and above responded well to hormone treatment.The ovulation time ranged from 72 to 144 hrs. The fertilization rate was about19% and hatching rate was 5-10%. Mortality of larvae was noticed on 4th and7th days after hatching. Females were converted to oozing males in 6 – 9 monthsby oral administration of 17α methyl testosterone hormone on alternate days @2.0 mg/kg body weight.